2002
DOI: 10.1006/bulm.2002.0303
|View full text |Cite
|
Sign up to set email alerts
|

A Two-Variable Model of Somatic–Dendritic Interactions in a Bursting Neuron

Abstract: We present a two-variable delay-differential-equation model of a pyramidal cell from the electrosensory lateral line lobe of a weakly electric fish that is capable of burst discharge. It is a simplification of a six-dimensional ordinary differential equation model for such a cell whose bifurcation structure has been analyzed (Doiron et al., J. Comput. Neurosci., 12, 2002). We have modeled the effects of back-propagating action potentials by a delay, and use an integrate-and-fire mechanism for action potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 48 publications
1
19
0
Order By: Relevance
“…Somatodendritic ping-pong has been previously described in the context of neuronal bursting dynamics [2,9,20,28,39]. Bose and Booth [2] showed that in order for somatodendritic ping-pong bursting activity to occur in two-compartment models, the coupling conductance between the somatic and dendritic compartments and the integration time constant of the dendritic compartment must be tightly tuned so as to allow the dendritic compartment time to be sufficiently depolarized after a somatic spike.…”
Section: Linear Spikementioning
confidence: 99%
“…Somatodendritic ping-pong has been previously described in the context of neuronal bursting dynamics [2,9,20,28,39]. Bose and Booth [2] showed that in order for somatodendritic ping-pong bursting activity to occur in two-compartment models, the coupling conductance between the somatic and dendritic compartments and the integration time constant of the dendritic compartment must be tightly tuned so as to allow the dendritic compartment time to be sufficiently depolarized after a somatic spike.…”
Section: Linear Spikementioning
confidence: 99%
“…In (9), differentiation is with respect to r . We note that c and s act as parameters in the v d equation, and that s = 0 reduces the Ca equation to a simple equation of exponential decay.…”
Section: Burst Initiationmentioning
confidence: 99%
“…Suppose that a term -I s y n = -g s y n S i n h [ V d -E i n h ] were added to the right side of the u$ equation in ( l ) , (9) or (10). Sinh is a synaptic gating variable which, at the moment of a pre-synaptic spike (or burst), is reset to one and then decays like exp(-Kt) for some decay rate K .…”
Section: Burst Initiationmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, computational neuroscientists have begun to use integrate-and-fire methods to model phenomenon such as bursting and calcium oscillations (Coombs et al, 2001;Laing and Longtin, 2002;Liu and Wang, 2001;or van Vreeswijk and Hansel, 2001). Here we consider excitatory networks consisting of RS and IB cortical neurons as described in McCormick et al (1985).…”
Section: Introductionmentioning
confidence: 99%